2011
DOI: 10.7205/milmed-d-10-00056
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study of the Effect of a Diagnosis of Concussion on PTSD Symptoms and Other Psychiatric Variables at the Time of Treatment Seeking Among Veterans

Abstract: The aim of this study was to assess whether a diagnosis of concussion given at a Veterans Healthcare Administration secondary traumatic brain injury assessment impacted either posttraumatic stress disorder (PTSD) symptomatology or other variables at the time veterans sought treatment for PTSD. This retrospective study compared 61 male veterans with a history of military-related concussion and military-related PTSD to 83 male veterans with military-related PTSD but without a diagnosis of military-related concus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
1
7
1
Order By: Relevance
“…In another study, probable PTSD was more likely in subjects who had more severe mild brain injuries than in those with brain injuries with alteration of consciousness only and those with no injuries at all . Contrary to the above findings, there were no differences in rates of PTSD found based on severity of TBI (MacGregor et al, 2010;Romesser et al, 2011).…”
Section: Rates Of Ptsdcontrasting
confidence: 98%
See 1 more Smart Citation
“…In another study, probable PTSD was more likely in subjects who had more severe mild brain injuries than in those with brain injuries with alteration of consciousness only and those with no injuries at all . Contrary to the above findings, there were no differences in rates of PTSD found based on severity of TBI (MacGregor et al, 2010;Romesser et al, 2011).…”
Section: Rates Of Ptsdcontrasting
confidence: 98%
“…More than 10 different measures from the Veterans Affairs Military Stress Treatment Assessment were used to evaluate concussion and PTSD interactions. Those in the concussed group had more difficulties dealing with their PTSD, increased pain, and a greater number of days that they reported medical problems (Romesser et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…A case–control study examining all suicide deaths among those serving in the United States military with moderate risk of bias did not show a significantly higher rate of TBI among those who died by suicide ( 13 ). Two studies examining whether Veterans with comorbid PTSD and mild TBI had an increased likelihood of suicidal behaviors as compared to Veterans with PTSD alone reported non-significant results and had high risk of bias ( 14 , 15 ). Another study found a significantly higher rate of suicide ideation among patients with TBI as compared to healthy controls with moderate risk of bias ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of TBI severity, however, injured patients with PTSD demonstrate the greatest impairment based on self-report (Zatzick et al, 2010) and endorsed decreased ability to cope with the PTSD symptoms compared combat veterans without a TBI (Romesser et al, 2011). In a study directly comparing cohorts of TBI patients, those with a dual diagnosis of depression performed poorly on tests of frontotemporal functioning (Trail Making B, WCST), had lower choline/creatine and N-acetylaspartate/creatine ratios in right basal ganglia based on MRS, and lower regional brain volumes in the right frontal, left occipital and temporal lobes (Rao et al, 2010).…”
Section: Frequently Used Research Designs In the Study Of The Psychopmentioning
confidence: 99%
“…Such cross sectional study designs have been used to explore variables as gender and the number of sport concussions (Cantu, Guskiewicz, & Register-Mihalik, 2010;Frommer et al, 2011;Matser et al, 1999), cognitive deficits in persistent postconcussive syndrome (e.g. Cicerone & Azulay, 2002) and psychiatric comorbidities of PTSD and depression with moderate and severe TBI (Romesser et al, 2011;Zatzick et al, 2010). In comparing 812 sports concussions across nine competitive sports, male athletes were more likely to report symptoms of amnesia, confusion and disorientation, while female athletes reported more drowsiness and sensitivity to noise than did males (Frommer et al, 2011).…”
Section: Frequently Used Research Designs In the Study Of The Psychopmentioning
confidence: 99%